STRUCTURE OF SUPER QUARTZITE AT THE BURAL-SARDYK DEPOSIT, EAST SAYAN MOUNTAINS - А. М. Mazukabzov; А. М. Fedorov; A. I. Nepomnyashchikh (Геодинамика и тектонофизика)
The article presents the results of geological and structural studies of the northwestern part of the Gargan quartziferous province, wherein the Bural-Sardyk deposit is located. The early views on this deposit of high-quality siliceous raw materials have been amended using the new data. This deposit is associated with quartzites of the Meso-Proterozoic Irkut formation and discordantly overlaps the Gargan block. According to the detailed study results on the cover of the Oka-Urik interfluve area, its structure is predetermined by physical and mechanical properties of the rocks, and the degree of rock dislocation depends on the rock viscosity. Most of its section is composed of viscous quartzites that create the structural framework of the study area. Such viscous rocks are not prone to folding. An alternative is detachment taking place concordantly to layering. The only interlayer is composed of limestones that underwent intense plastic deformation reflected in multi-folding. Actually, limestones mark a zone of plastic detachment. The authors propose an interpretation of the formation of the deposit structure. The main deformation event was preceded by the sediment transformation stage in conditions of diagenesis and catagenesis due to the influence of a lithostatic load. Primary recrystallization under lithogenesis led to the formation of high-purity silicon rocks. At the next stage, the rocks were subjected to longitudinal compression in the PT conditions of green-shale metamorphism. This stage is mainly evidenced by sublayer detachments. In parallel with that process, quartzites experienced super-plastic flow and recrystallization, which led to the formation of super-quartzites. The bodies of super-quartzites tend to be layered and less discordant. Such a structural position suggests the possibility of detecting latent manifestations of super-quartzites at different levels in the quartzites of the Irkut formation. Tectonic detachments are observed in the sedimentary cover and do not reach the foundation. Based on these features, there are reasons to use the thin-skinned tectonic model. Rock deformation occurred under stress oriented from the northwest to the southeast. This is indicated by the position of the axial surfaces of the folds, as well as the orientations of the maximum compression axis and the crystallographic axes of quartz. Macro- and microstructural data indicate that the tectonic transport of matter was directed to the southeast. The research results were used for compiling a new geological map of the deposit.